Fine Chemicals by Reductive Carbonylation of Nitroarenes, Catalyzed by Transition Metal Complexes - Ragaini, Fabio; Cenini, Sergio; Gallo, Emma; Caselli, Alessandro; Fantauzzi, Simone (Current Organic Chemistry, 2006)
The application of reductive carbonylation of nitroarenes to the synthesis of fine chemicals is described. The review focuses on the results reported from 1996 onwards and is mainly divided in two parts, respectively describing the intra-molecular cyclization reactions of nitroarenes bearing in the ortho position a suitable functional group and the intermolecular reactions of nitroarenes with external olefins and alkynes. Benzo-fused heterocycles such as indoles and quinolinones are obtained by the first group of reactions, whereas allylic amines, oxazines, pyrroles and indoles are the products of inter-molecular reactions. Mechanistic studies are also discussed in a separate section. x
Keywords: trifluoroacetate